Association between blood metal exposures and hyperuricemia in the U.S. general adult: A subgroup analysis from NHANES. (March 2023) - Tan, Yuxuan; Fu, Yingyin; Huang, Feng; Wen, Lin; Weng, Xueqiong; Yao, Huojie; Liang, Huanzhu; Kuang, Mincong; Jing, Chunxia
Abstract: Background: The relationship between metal exposure and hyperuricemia is still controversial, especially in certain population groups. Methods: This cross-sectional study included adults from NHANES 2011–2016. Seven metals, including Pb, Cd, Hg, Mn, Se, Cu, and Zn, were detected in blood by ICP‒MS. Multivariable logistic regression, LASSO, and BKMR models were used to assess the effects of single and mixed metal exposures and hyperuricemia. Moreover, this association was analyzed by sex, BMI, and age. Results: A total of 4074 individuals were included in our final analysis, and 825 (20.3%) people were classified as having hyperuricemia. In logistic regression, Pb (Q4: OR [95% CI]: 1.50 [1.00, 2.24]) was associated with hyperuricemia after adjusting for all covariates. LASSO penalized regression analysis further indicated positive associations of lead and zinc with hyperuricemia. In BKMR analysis, U-shaped dose‒response curves were generated for Se, Mn, Cu, and Zn when fixing the other metals in the 50th percentile. A significant positive trend was found between mixed metal exposure and hyperuricemia, in which blood Se, Zn, and Cd had the highest PIP (PIP = 0.651, 0.549, and 0.530, respectively). In weighted logistic regression, subgroup analyses revealed a significant association between Pb and hyperuricemia among the non-overweight group. Significant positive trends between mixed metals and hyperuricemia were found in the male and non-overweight groups in the BKMR models. Conclusion: Our study suggests that a higher concentration of mixed metal might increase the risk of hyperuricemia in U.S. adults. Males and people with a BMI under 25 are more likely to be affected. Graphical abstract: Image 1 Highlights: The association between metals exposure and hyperuricemia in the subgroup populations remains unknown. Lead was significant positive associated with hyperuricemia. There was a positive trend between hyperuricemia and mixed metals, which Zn, Cd, and Se contributed the most. The positive relationship was more pronounced in men and non-overweight groups.